PENERAPAN APLIKASI ARCGIS DALAM PEMBUATAN PETA TOPOGRAFI PADA PENDIDIKAN NAVIGASI DARAT MPA JAMARSINGSIA IAIN BUKITTINGGI - Ilham Rosia; Sarwo Derta; Liza Efriyanti; Riri Okra (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the author discusses the title because MPA Jamarsingsia in field practice still uses one topographic map simultaneously and the coverage area is quite wide, with the lack of field practice equipment causing difficulties for members and instructors in carrying out land navigation field education. The main issue that the authors study in the research in this thesis is how to design a topographic map using the ArcGIS application that is able to produce contour lines precisely and accurately. The general objective to be achieved in this research is to determine the design of a topographic map using the ArcGIS application that is able to produce precise and accurate contours. This research is a research with the RnD (Research and Development) method with the research method used to produce a particular product and test the effectiveness of a product. This RnD research uses the Luther-Sutopo version of the multimedia development model. The stages in Luther-Sutopo's research are concept (conception), design (design), Material collecting (data collection), assembly (manufacture), testing (testing), and distribution (distribution). This study produced a topographic map of Ngarai Sianok with a scale of 1:6000 and a 10-meter interval between contour lines and a topographic map of the IAIN Bukittinggi area with a scale of 1:500 and an interval between contour lines of 5 meters for media in Land Navigation Education MPA Jamarsingsia. Based on the results of the validity, practicality and effectiveness test, it is stated that the topographic map that the author designed in this study was declared very valid with an average value of 0.92, very practical with an average value of 0.96 and very effective with an average value of 0.79 . Keywords: ArcGIS Applications, Topographic Maps, Land Navigation Keywords: ArcGIS Applications, Topographic Maps, Land Navigation